GROUND WATERS DISPOSAL MODELING DURING THE INFRASTRUCTURAL GEOTECHNICAL SYSTEMS DEVELOPMENT - Татарко, Лариса; Дякун, Инна; Дзюба, Сергей; Киричко, Сергей (SWorldJournal, 2020)
As a rule, the technologies for the development of infrastructural geotechnical systems are associated with the processes of nearby territories flooding and the formation of appropriate technological conditions, which determine the main sources of groundw